Desenvolvimento de ferramenta computacional na avaliação econômica entre sistemas renováveis de geração de energia elétrica conectados à rede para propriedades rurais - Ozanski, Adrielle Cristina (2024)
The main objective of this study was to develop a computational tool for economic comparison between grid-connected photovoltaic, wind and biogas energy generation systems for rural properties. The study aims to assist rural producers in choosing the renewable energy generation system that offers the best cost/benefit ratio. Initially, data were collected on the characteristics of the rural properties and the resources available for sizing each system. Subsequently, the costs of implementation, maintenance and operation of the energy generation alternatives were estimated. With this information, the LCOE of each system was calculated, allowing accurate comparisons regarding economic viability. Based on the sizing and economic analysis script, computational routines were developed using the C# and JavaScript languages. These routines gave rise to an easily accessible online platform, made available through a public website. The tool offers an intuitive and user-friendly interface, allowing users to size the systems and make economic comparisons between them in a practical, fast and efficient manner. The results of the simulations indicated that the photovoltaic solar system is the best investment option among the alternatives analyzed. The wind system also stood out as a competitive option compared to the biodigester, mainly due to the high costs associated with the latter. The results showed the importance of carrying out careful analyses when planning investments. With the help of the tool, each alternative can be studied carefully, preventing investors from creating a misconception about the economic viability of the project. Furthermore, it is expected that this approach will contribute to the adoption of renewable energy in rural areas, promoting efficiency and sustainability.